MODELLING AND SIMULATION OF FUELS PRODUCTION FROM SYNGAS - PETRESCU, Letitia; IMRE-LUCACI, Arpad; BERCI, Cristina Izabella (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Syngas is a very important product, with a variety of uses; it may even become a primary source of fuel, and replace natural gas. This is because syngas has the building blocks to create all the products and chemicals currently generated in the petrochemical industry. Fuels manufactured from synthesis gas offer special opportunities based both on environmental and energy performance. The aim of the present work is to design and compare different chemical production processes for fuels generation using syngas as raw material. ChemCAD process simulator software was used as the main tool for process modelling and simulation. The investigation was focused on the conversion of syngas to methanol, dimethyl ether and hydrogen at a large scale. For comparison reasons, the same amount of syngas (e.g. 10000 kmol/h) was used in all three cases under investigation. After comparison, syngas to hydrogen process seems to be the best option from thermal energy point of view and in terms of environmental impact.